Система підтримки прийняття рішень, що функціонує в режимі автоматичної класифікації - Стадник, Ганна Анатоліївна (НТУ "ХПІ", 2016)
Розглядається інформаційно-екстремальний алгоритм функціонування системи підтримки прийняття рішень в режимі автоматичної класифікації. При цьому запропонований алгоритм дозволяє на етапі самонавчання системи автоматично формувати вхідну навчальну матрицю, а на етапі екзамену, тобто безпосередньо в робочому режимі, виділяти новий клас розпізнавання і здійснювати донавчання системи. Реалізацію запропонованого алгоритму здійснено на прикладі діагностування опортуністичних інфекцій у ВІЛ-інфікованих осіб.

The process of input data automation classification is considered in the framework of information-extreme intelligence technology, which is based on maximizing the information capacity of the recognition system in the process of its machine learning. The proposed algorithm allows forming the input matrix in the mode of system self-learning and allocation of a new pattern in the mode of system examination. This system operation algorithm implements the modified k-means method for binary Hamming space in the mode of cluster analysis and forms the set of unrecognized patterns in the mode of factor cluster analysis, which is based on statistical criteria for the stability and homogeneity. If representativeness condition of formed set is fulfilled in the exam mode, it is added to the input matrix. The resulting retraining system is implemented for advanced classes’ recognition alphabet. Optimization of the decision support system learning parameters is carried out by searching global maximum of the Kullback information criterion, which is calculated in the working (acceptable) domain of its function. Implementation of the proposed algorithm is executed by the example of opportunistic infections diagnosis in HIV-infected people.
Decision Support System, functioning in the automatic classification
Keywords: автоматична класифікація; факторний кластер-аналіз; оптимізація; інформаційний критерій; опортуністична інфекція; decision support system; cluster analysis; factor cluster analysis; optimization; information criterion; opportunistic infection